2020
DOI: 10.34105/j.kmel.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis and scientific mapping of the e-learning literature from 1995 to 2018

Abstract: This study aims to explore the research trends in the field of e-learning by analyzing the relevant publications using network analysis and scientific mapping. The data were extracted from the Web of Science database from 1995 to 2018, revealing a growing number of articles published in e-learning. The keywords “e-learning” and “Internet” ranked first and second as the most frequently used terminology. “Internet”, “Blended Learning” and “E-Learning” are recognized as three main categories in the field. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The linkages between documents are visualized in a graph form, allowing network analysis to be carried out to obtain information about activities on the research map [8]. Various measures are used for network analysis, such as centrality, representing the strength of an edge and node in the network based on their role and position [20].…”
Section: Introductionmentioning
confidence: 99%
“…The linkages between documents are visualized in a graph form, allowing network analysis to be carried out to obtain information about activities on the research map [8]. Various measures are used for network analysis, such as centrality, representing the strength of an edge and node in the network based on their role and position [20].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific mapping of existing literature and a systematic literature review have recently become the field of highest interest to researchers. Scientific production and research output are pillars of any country's growth and development (Negahban and Zarifsanaiey, 2020). Most organisational decisions are governed by the critical fact that a basic scientific mapping and clear premises of the existing literature are conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Based on data from the Web of Science (WoS), Park and Shea (2020) conducted a co-citation study of online learning research trends over the past 10 years and discovered features and changes in research trends in online learning as well as the most cited publications in the field. Based on the WoS database from 1995 to 2018, Negahban and Zarifsanaiey (2020) investigated the research trends in the field of e-learning by assessing relevant studies employing network analysis and scientific mapping techniques and identified the most frequently used terminology, the greatest impact studies, and some topics that served as bridges to connect different topics. Based on the CNKI database from 2000 to 2021, Chi (2021) analyzed the number distribution of blended learning literature, core authors, and research institutions, and further conducted keyword co-occurrence analysis, emergence detection analysis, and cluster time domain mapping analysis by using the knowledge mapping tool CiteSpace.…”
Section: Introductionmentioning
confidence: 99%